3D reconstruction of MR‐visible Fe3O4‐mesh implants: Pelvic mesh measurement techniques and preliminary findings. Issue 1 (2nd November 2018) - Brocker, Kerstin A.; Mokry, Theresa; Alt, Céline D.; Kauczor, Hans‐Ulrich; Lenz, Florian; Sohn, Christof; DeLancey, John O.; Chen, Luyun
Abstract : Aims: To develop MR‐based measurement technique to evaluate the postoperative dimension and location of implanted magnetic resonance (MR)‐visible meshes. Methods: This technique development study reports findings of six patients (A‐F) with cystoceles treated with anterior vaginal MR‐visible Fe3 O4 ‐polypropylene implants. Implanted meshes were reconstructed from 3 months and/or 1 year postsurgical MR‐images using 3D Slicer®. Measurements including mesh length, distance to the ischial spines, pudendal, and obturator neurovascular bundles and urethra were obtained using software Rhino® and a custom Matlab® program. The range of implanted mesh length and their placements were reported and compared with mesh design and implantation recommendations. With the anterior/posterior‐mesh‐segment‐ratio mesh shrinkage localization was evaluated. Results: Examinations were possible for patients A‐D 3 months and for A, C, E, and F 1 year postsurgical. The mesh was at least 40% shorter in all patients 3 months and/or 1 year postoperatively. A, B showed shrinkage in the anterior segment, D, E in the posterior segment (Patients C, F not applicable due to intraoperative mesh trimming). Patient E presented pain in the area of mesh shrinkage. In Patient C posterior mesh fixations were placed in the iliococcygeal muscle rather than sacrospinous ligaments. Arm placement less than 20 mm from the pudendal neurovascular bundles was seen in all cases. The portion of the urethra having mesh underneath it ranged from 19% to 55%. Conclusions: MRI‐based measurement techniques have been developed to quantify implanted mesh location and dimension. Mesh placement variations possibly correlating with postoperative complications can be illustrated.